2021
DOI: 10.3390/jtaer16040038
|View full text |Cite
|
Sign up to set email alerts
|

Online Reviews and Product Sales: The Role of Review Visibility

Abstract: When studying the impact of online reviews on product sales, previous scholars have usually assumed that every review for a product has the same probability of being viewed by consumers. However, decision-making and information processing theories underline that the accessibility of information plays a role in consumer decision-making. We incorporate the notion of review visibility to study the relationship between online reviews and product sales, which is proxied by sales rank information, studying three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 108 publications
4
17
0
Order By: Relevance
“…Although this result differs from the previous study (Ghose and Ipeirotis, 2011), it is in line with the results from other studies, which indicate that more readable texts generate a positive marketing outcome: they are positively associated with helpfulness (Fang et al, 2016;Korfiatis et al, 2012;Liu and Park, 2015;Reinartz, 2016). This discrepancy may be due to the explosive growth of customer review volume in e-commerce platforms in recent years leads to information overload, which forces customers to select reviews to read (Alzate et al, 2021b). In this case, more readable reviews enjoy more helpfulness (Fang et al, 2016;Korfiatis et al, 2012;Liu and Park, 2015;Reinartz, 2016), which consequently leads to more product sales (Kaushik et al, 2018).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Although this result differs from the previous study (Ghose and Ipeirotis, 2011), it is in line with the results from other studies, which indicate that more readable texts generate a positive marketing outcome: they are positively associated with helpfulness (Fang et al, 2016;Korfiatis et al, 2012;Liu and Park, 2015;Reinartz, 2016). This discrepancy may be due to the explosive growth of customer review volume in e-commerce platforms in recent years leads to information overload, which forces customers to select reviews to read (Alzate et al, 2021b). In this case, more readable reviews enjoy more helpfulness (Fang et al, 2016;Korfiatis et al, 2012;Liu and Park, 2015;Reinartz, 2016), which consequently leads to more product sales (Kaushik et al, 2018).…”
Section: Discussionsupporting
confidence: 67%
“…The rationale behind this approach is that the log curves between sales ranking and actual product sales are approximately linear (Chevalier and Goolsbee, 2003). Besides, this approach is also in line with previous empirical studies, in which product sales on e-commerce platforms is the dependent variable (Alzate et al, 2021b;Chen et al, 2004;Chong et al, 2016;Cui et al, 2012;Kaushik et al, 2018).…”
Section: Operationalisation Measurement and Structural Modelsupporting
confidence: 59%
“…All independent variables are lagged one day in comparison to the dependent variable to be able to test how changes in ratings and reviews impact downloads, as a causality procedure. A one-day lag was used rather than additional days as related work has found that consumers rely only or to a greater extent on most recent reviews (Li et al 2019;Alzate et al 2021). Inspection of our data set reveals that reviews and ratings change on a daily basis, and along with the aforementioned literature arguments, it motivates the use of a one-day lag.…”
Section: Variables and Measurementmentioning
confidence: 88%
“…Visibility comprises two items: one referring to the promotional materials related to FDAs (promotion) and the recommendations received from other people who use such applications (also known in the literature as a social influence). Alzate, Arce-Urriza, and Cebollada [ 36 ] discuss the importance of review visibility for the buying decision, a form of word-of-mouth advertising. Boyland et al [ 37 ] analyse the influence of celebrities used in food consumption commercials.…”
Section: Literature Reviewmentioning
confidence: 99%